High-performance non-silicon heat-conducting gasket and preparation method thereof
By using hydrophobic MgO/ZnO composite thermal conduction powder in non-silicon systems, soft and tough non-silicon thermal conduction gaskets are prepared, which solves the problem of poor thermal conduction effect of existing non-silicon thermal conduction gaskets, significantly improves thermal conductivity and toughness, meets the needs of efficient heat dissipation and avoids silicon pollution.
Patent Information
- Application Number
- CN202411877848.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-14
AI Technical Summary
The existing non-silicon thermal conductivity gaskets have poor thermal conductivity under environments of high compression and thermal expansion, and have low rebound rate and poor thermal conductivity, making it difficult to meet the needs of efficient heat dissipation.
By filling the hydrophobic MgO/ZnO composite thermal conduction powder in the non-silicon system, a soft and tough non-silicon thermal conduction gasket was prepared. The method of zinc oxide coated with magnesium oxide avoided hydrolysis problems, enhanced the compatibility between the filler and the substrate, and improved the overall thermal conductivity.
It significantly improves the thermal conductivity and toughness of non-silicon thermal conductivity gaskets, can maintain good thermal conductivity under high compression and thermal expansion environments, reduce the risk of brittle fracture, improve heat dissipation performance and avoid the risk of contamination of silicon materials.
Smart Images

Figure BDA0005197387640000061
Abstract
Description
Technical Field
[0001] The invention belongs to the field of thermal conductive materials, and in particular relates to a high-performance non-silicon thermal conductive gasket and a preparation method thereof. Background Art
[0002] As electronic components and modules develop towards high integration and miniaturization, power density gradually increases, and the heat generated also increases. How to effectively dissipate heat has become a core challenge in design, especially under space-constrained conditions. As an important component of the heat dissipation system, thermal conductive materials are mainly used to fill the tiny gap between the heat source and the heat dissipation components, optimize the heat conduction path, and reduce the operating temperature of electronic components. Among the many thermal conductive materials, thermal conductive gaskets are widely used due to their good thermal conductivity, compressibility and convenient assembly characteristics. However, most thermal conductive gaskets on the market are still based on silicone. Although they have good thermal conductivity and ease of use, there are volatilization problems in some special application scenarios. The overflow of silicone oil may contaminate the equipment and affect the electrical performance. In this context, non-silicon thermal conductive gaskets have gradually received attention. Although non-silicon materials can avoid the problem of silicon volatilization, traditional non-silicon thermal conductive gaskets often have shortcomings such as low rebound rate and poor thermal conductivity. Especially in situations where the gap size changes greatly due to thermal expansion, its performance is difficult to meet the needs of efficient heat dissipation.
[0003] In this technical context, non-silicon thermally conductive gaskets with good softness and toughness have become an urgent need in the current technical field. This type of non-silicon thermally conductive gasket can not only ensure good thermal conductivity under high compression and thermal expansion changes, but its softness and toughness can also effectively adapt to more complex assembly requirements, improving the applicability and reliability of thermal interface materials. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a high-performance non-silicon thermally conductive gasket and a preparation method thereof. The non-silicon thermally conductive gasket is prepared by filling a hydrophobic MgO / ZnO composite thermally conductive powder in a non-silicon system. The prepared non-silicon gasket is soft and tough at the same time, and has excellent tensile strength. It can effectively improve the heat dissipation performance of electronic equipment while avoiding the pollution risk of traditional silicon-based materials.
[0005] To achieve the above purpose, the present invention provides a high-performance non-silicon thermally conductive gasket, comprising the following preparation steps: putting 100 parts of modified acrylic copolymer into a planetary mixer, adding 100-350 parts of hydrophobic MgO / ZnO composite thermally conductive powder and 10-40 parts of boron nitride, mixing and stirring for 1-2 hours, taking out and performing vacuum degassing, and then hot pressing to obtain a non-silicon thermally conductive gasket of a certain thickness.
[0006] The preparation steps of the hydrophobic MgO / ZnO composite thermally conductive powder are as follows: (1) Preparation of MgO / ZnO composite thermal conductive powder: 50 g of zinc acetate and 10 g of magnesium sulfate were added to 100 mL of distilled water and stirred for 10 min to obtain a mixed solution A; 70 g of potassium hydroxide and 30 g of n-propylamine were added to 100 mL of distilled water, stirred for 10 min, and then the solution was added to the mixed solution A, and the mixture was transferred to a reactor, heated at 180° C. for 15 h, naturally cooled to room temperature, filtered, washed with distilled water and ethanol for 3 times, respectively, and dried at 60° C. for 12-24 h to obtain MgO / ZnO powder. (2) Preparation of hydrophobic MgO / ZnO composite thermally conductive powder: Take 50 g of MgO / ZnO powder from step (1) and add it to 100 mL of ethanol solution. After stirring for 10 min, add 5 g of octadecanoic acid, stir at 100° C. for 30 min, and then transfer to a vacuum oven and bake at 60° C. for 5 h to obtain a hydrophobic MgO / ZnO composite thermally conductive powder.
[0007] The preparation steps of the modified acrylic copolymer are as follows: 90 parts of acrylic acid monomer, 10 parts of acrylic acid functional monomer and 1-15 parts of dioctyl phthalate are polymerized under light initiation conditions to obtain an acrylic acid copolymer, and then 0.1-0.5 parts of hexamethylene diisocyanate are added to react at 80° C. for 1-2 hours, and vacuum degassing is performed to obtain the modified acrylic copolymer.
[0008] The acrylic acid monomer is one of octyl acrylate and 2-diethylhexyl acrylate, or a mixture of the two.
[0009] The acrylic acid functional monomer is hydroxyoctyl acrylate.
[0010] The median diameter D50 of the boron nitride is 150-200 μm.
[0011] The thickness of the non-silicon gasket is 0.5 mm to 5 mm, and the size can be determined according to specific application requirements.
[0012] The thermal conductivity of the non-silicon thermally conductive film is above 0.5 W / m·K.
[0013] The beneficial effects of the present invention are as follows: (1) The hydrophobic MgO / ZnO composite thermally conductive powder used in the present invention has excellent thermal conductivity, but it is prone to hydrolysis in a humid environment, resulting in a decrease in thermal conductivity. By coating zinc oxide on the surface of magnesium oxide, not only is the hydrolysis problem of magnesium oxide effectively avoided, but the lubricating effect of zinc oxide greatly improves the compatibility of the filler and the substrate, reducing the interface thermal resistance; the hydrophobic layer on the surface further enhances the dispersibility and fluidity of the composite powder, improving the overall thermal conductivity. (2) Compared with traditional single fillers, the hydrophobic MgO / ZnO composite thermal conductive powder can be more evenly dispersed in the resin matrix. The synergistic effect between its components improves the cohesion of the non-silicon system, improves its tensile strength without significantly reducing the toughness of the material, significantly reduces the risk of brittle fracture of the gasket in a high temperature environment, and maintains good physical property stability. DETAILED DESCRIPTION
[0014] In order to introduce the present invention in more detail, the present invention is further described and illustrated in conjunction with the following examples.
[0015] Example 1 (1) Preparation of hydrophobic MgO / ZnO composite thermal conductive powder Preparation of MgO / ZnO composite thermal conductive powder: Add 50g of zinc acetate and 10g of magnesium sulfate to 100mL of distilled water, stir for 10min to obtain a mixed solution A; add 70g of potassium hydroxide and 30g of n-propylamine to 100mL of distilled water, stir for 10min, add the solution to the mixed solution A, and transfer to a reactor, heat to react at 180°C for 15h, cool naturally to room temperature, filter, wash with distilled water and ethanol for 3 times respectively, and dry at 60°C for 18h to obtain MgO / ZnO powder. Preparation of hydrophobic MgO / ZnO composite thermally conductive powder: Take 50 g of MgO / ZnO powder from step (1) and add it to 100 mL of ethanol solution. After stirring for 10 min, add 5 g of octadecanoic acid, stir at 100 °C for 30 min, and then transfer to a vacuum oven and bake at 60 °C for 5 h to obtain a hydrophobic MgO / ZnO composite thermally conductive powder. (2) Preparation of modified acrylic copolymer 90 parts of octyl acrylate, 10 parts of hydroxyoctyl acrylate and 3 parts of dioctyl phthalate were polymerized under photoinitiation conditions to obtain an acrylic copolymer, and then 0.4 parts of hexamethylene diisocyanate were added to react at 80°C for 2 hours, and vacuum degassing was performed to obtain a modified acrylic copolymer. (3) Preparation of high-performance non-silicon thermal conductive film 100 parts of modified acrylic copolymer were put into a planetary mixer, and 350 parts of hydrophobic MgO / ZnO composite thermal conductive powder and 40 parts of boron nitride with a D50 of 150 μm were added and mixed for 2 hours. The mixture was taken out for vacuum degassing and then hot-pressed to obtain a 2 mm thick non-silicon thermal conductive gasket.
[0016] Example 2 (2) Preparation of hydrophobic MgO / ZnO composite thermal conductive powder Preparation of MgO / ZnO composite thermal conductive powder: Add 50g of zinc acetate and 10g of magnesium sulfate to 100mL of distilled water, stir for 10min to obtain a mixed solution A; add 70g of potassium hydroxide and 30g of n-propylamine to 100mL of distilled water, stir for 10min, add the solution to the mixed solution A, and transfer to a reactor, heat to react at 180°C for 15h, cool naturally to room temperature, filter, wash with distilled water and ethanol for 3 times respectively, and dry at 60°C for 18h to obtain MgO / ZnO powder. Preparation of hydrophobic MgO / ZnO composite thermally conductive powder: Take 50 g of MgO / ZnO powder from step (1) and add it to 100 mL of ethanol solution. After stirring for 10 min, add 5 g of octadecanoic acid, stir at 100 °C for 30 min, and then transfer to a vacuum oven and bake at 60 °C for 5 h to obtain a hydrophobic MgO / ZnO composite thermally conductive powder. (2) Preparation of modified acrylic copolymer 90 parts of octyl acrylate, 10 parts of hydroxyoctyl acrylate and 10 parts of dioctyl phthalate were polymerized under photoinitiation conditions to obtain an acrylic copolymer, and then 0.2 parts of hexamethylene diisocyanate were added to react at 80°C for 1.5 hours, and vacuum degassing was performed to obtain a modified acrylic copolymer. (3) Preparation of high-performance non-silicon thermal conductive film 100 parts of modified acrylic copolymer were put into a planetary mixer, and 200 parts of hydrophobic MgO / ZnO composite thermal conductive powder and 20 parts of boron nitride with a D50 of 180 μm were added and mixed and stirred for 1 hour. The mixture was taken out for vacuum degassing, and then hot-pressed to obtain a 2 mm thick non-silicon thermal conductive gasket.
[0017] Example 3 (1) Preparation of hydrophobic MgO / ZnO composite thermal conductive powder Preparation of MgO / ZnO composite thermal conductive powder: Add 50g of zinc acetate and 10g of magnesium sulfate to 100mL of distilled water, stir for 10min to obtain a mixed solution A; add 70g of potassium hydroxide and 30g of n-propylamine to 100mL of distilled water, stir for 10min, add the solution to the mixed solution A, and transfer to a reactor, heat to react at 180°C for 15h, cool naturally to room temperature, filter, wash with distilled water and ethanol for 3 times respectively, and dry at 60°C for 18h to obtain MgO / ZnO powder. Preparation of hydrophobic MgO / ZnO composite thermally conductive powder: Take 50 g of MgO / ZnO powder from step (1) and add it to 100 mL of ethanol solution. After stirring for 10 min, add 5 g of octadecanoic acid, stir at 100 °C for 30 min, and then transfer to a vacuum oven and bake at 60 °C for 5 h to obtain a hydrophobic MgO / ZnO composite thermally conductive powder. (2) Preparation of modified acrylic copolymer 90 parts of 2-diethylhexyl acrylate, 10 parts of hydroxyoctyl acrylate and 5 parts of dioctyl phthalate were polymerized under photoinitiation conditions to obtain an acrylic copolymer, and then 0.5 parts of hexamethylene diisocyanate were added to react at 80°C for 2 hours, and vacuum degassing was performed to obtain a modified acrylic copolymer. (3) Preparation of high-performance non-silicon thermal conductive film 100 parts of modified acrylic copolymer were put into a planetary mixer, and 250 parts of hydrophobic MgO / ZnO composite thermal conductive powder and 40 parts of boron nitride with a D50 of 200 μm were added and mixed and stirred for 1.5 hours. The mixture was taken out for vacuum degassing and then hot-pressed to obtain a 2 mm thick non-silicon thermal conductive gasket.
[0018] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the hydrophobic MgO / ZnO composite thermally conductive powder is not prepared, and the 350 parts of hydrophobic MgO / ZnO composite thermally conductive powder in step (3) of Example 1 are replaced by 300 parts of D50 (30 μm magnesium oxide + 50 parts of 5 μm zinc oxide), and the other steps are consistent with steps (2) and (3) of Example 1.
[0019] Comparative Example 2 The difference between Comparative Example 1 and Example 1 is that the hydrophobic MgO / ZnO composite thermally conductive powder is replaced by MgO / ZnO composite thermally conductive powder, and the MgO / ZnO composite thermally conductive powder is not subjected to hydrophobic treatment. The other steps are consistent with steps (1)(2)(3) of Example 1.
[0020] Comparative Example 3 The difference between Comparative Example 1 and Example 1 is that hydrophobic MgO / ZnO composite thermally conductive powder is not prepared, and 350 parts of hydrophobic MgO / ZnO composite thermally conductive powder in step (3) of Example 1 are replaced by 350 parts of alumina with a D50 of 30 μm, and the other steps are consistent with steps (2) and (3) of Example 1.
[0021] The performance tests were conducted on the non-silicon thermally conductive pads of Examples 1 to 3 and Comparative Examples 1 to 3. The test results are shown in Table 1.
[0022] Performance test thermal conductivity: refer to standard ASTM D5470 and use DRL-III thermal conductivity tester of Xiangtan Xiangyi Instrument Co., Ltd. for testing. The sample diameter is 3cm and the thickness is 2mm. Thermal conductivity test after high and low temperature impact test: Place the sample in a high and low temperature impact test chamber, with the high temperature at 120°C and the low temperature at -40°C, and each high and low temperature is maintained for 30 minutes as one cycle, for a total of 168 cycle tests. After taking out, place it in room temperature for 2 hours before conducting a thermal conductivity test. Tensile strength and elongation at break: refer to standard GB / T 1040, tested using UTM-1422 universal testing machine from Chengde Jinjian Testing Instrument Co., Ltd. Fold 180°: Take a 50*50mm non-silicone thermal pad and fold it along the center line. After folding it to 180°, release the force and observe the status of the pad.
[0023] Table 1
[0024] From the data in Table 1, it can be seen that the non-silicon organosilicon gaskets prepared in Examples 1-3 have good thermal conductivity and toughness, and still maintain good thermal conductivity after the hot and cold shock test. In Example 1, the thermal conductivity retention rate of the non-silicon gasket decreased from 96.82% to 75.62%, indicating the stability of the gasket after the hydrophobic MgO / ZnO composite thermal conductive powder is used in the present invention; in Example 1, the tensile strength of the non-silicon gasket increased by 29.51% and 96.80% respectively, and the elongation at break increased by 23.43% and 79.38% respectively, and it can be folded 180° without cracking.
[0025] This embodiment combines specific preferred implementation modes to explain the present invention in more detail, but does not mean that the specific implementation modes of the present invention are limited to these. For ordinary technicians in this technical field, some reasonable deductions or changes can be made without departing from the basic idea of the present invention, which should be regarded as within the scope of protection determined by the patent claims of the present invention.
Claims
1. A method for preparing a high-performance non-silicon thermally conductive pad, characterized in that: The method comprises the following preparation steps: putting 100 parts of modified acrylic copolymer into a planetary mixer, adding 100-350 parts of hydrophobic MgO / ZnO composite thermal conductive powder and 10-40 parts of boron nitride, mixing and stirring for 1-2 hours, taking out and performing vacuum degassing, and then hot pressing to obtain a non-silicon thermal conductive gasket of a certain thickness.
2. The method for preparing the high-performance non-silicon thermally conductive gasket according to claim 1, characterized in that: The preparation steps of the hydrophobic MgO / ZnO composite thermally conductive powder are as follows: (1) Preparation of MgO / ZnO composite thermal conductive powder: 50 g of zinc acetate and 10 g of magnesium sulfate were added to 100 mL of distilled water and stirred for 10 min to obtain a mixed solution A; 70 g of potassium hydroxide and 30 g of n-propylamine were added to 100 mL of distilled water, stirred for 10 min, and then the solution was added to the mixed solution A, and the mixture was transferred to a reactor, heated at 180° C. for 15 h, naturally cooled to room temperature, filtered, washed with distilled water and ethanol for 3 times, respectively, and dried at 60° C. for 12-24 h to obtain MgO / ZnO powder. (2) Preparation of hydrophobic MgO / ZnO composite thermally conductive powder: Take 50 g of MgO / ZnO powder from step (1) and add it to 100 mL of ethanol solution. After stirring for 10 min, add 5 g of octadecanoic acid, stir at 100° C. for 30 min, and then transfer to a vacuum oven and bake at 60° C. for 5 h to obtain a hydrophobic MgO / ZnO composite thermally conductive powder.
3. The method for preparing the high-performance non-silicon thermally conductive gasket according to claim 1, characterized in that: The preparation steps of the modified acrylic copolymer are as follows: 90 parts of acrylic acid monomer, 10 parts of acrylic acid functional monomer and 1-15 parts of dioctyl phthalate are polymerized under light initiation conditions to obtain an acrylic acid copolymer, and then 0.1-0.5 parts of hexamethylene diisocyanate are added to react at 80° C. for 1-2 hours, and vacuum degassing is performed to obtain the modified acrylic copolymer.
4. The method for preparing the high-performance non-silicon thermally conductive gasket according to claim 3, characterized in that: The acrylic acid monomer is one of octyl acrylate and 2-diethylhexyl acrylate, or a mixture of the two.
5. The method for preparing the high-performance non-silicon thermally conductive gasket according to claim 3, characterized in that: The acrylic acid functional monomer is hydroxyoctyl acrylate.
6. The method for preparing the high-performance non-silicon thermally conductive gasket according to claim 1, characterized in that: The median diameter D50 of the boron nitride is 150-200 μm.
7. The method for preparing the high-performance non-silicon thermally conductive gasket according to claim 1, characterized in that: The thickness of the non-silicon gasket is 0.5 mm to 5 mm, and the size can be determined according to specific application requirements.